Academic performance measurement: capacity building for OIC-Affiliated Universities - Abdul Aziz, Hassanuddeen; Nordin, Mohamad Sahari; Ismail, Ahmad Faris (Institute of Information System & Research Center, 2013)
The OIC recognises that performance measurement is an integral component of quality management of academic activities. The quality of performance measurement is vital to a university’s claim about the quality of its management of the curriculum, graduates, and research which define the trust and confidence of stakeholders and the general public. It is indisputable that in an institution of higher education, performance measurement is one of the major factors that influence the quality of faculty and student outcomes. Assessment shapes the learning, teaching and research that will take place; it molds what and how faculty will perform, and eventually what students will learn and how they will learn it. In sum, performance measurement is a catalyst for progress and reform in educational practices.